Large BRCA1 and BRCA2 genomic rearrangements in Malaysian high risk breast-ovarian cancer families - Kang, P.; Mariapun, S.; Phuah, S.Y.; Lim, L.S.; Liu, J.; Yoon, Sook-Yee; Thong, M.K.; Taib, N.A.M.; Yip, C.H.; Teo, Soo-Hwang (Kluwer (now part of Springer), 2010)
Early studies of genetic predisposition due to the BRCA1 and BRCA2 genes have focused largely on sequence alterations, but it has now emerged that 4-28% of inherited mutations in the BRCA genes may be due to large genomic rearrangements of these genes. However, to date, there have been relatively few studies of large genomic rearrangements in Asian populations. We have conducted a full sequencing and large genomic rearrangement analysis (using Multiplex Ligation-dependent Probe Amplification, MLPA) of 324 breast cancer patients who were selected from a multi-ethnic hospital-based cohort on the basis of age of onset of breast cancer and/or family history. Three unrelated individuals were found to have large genomic rearrangements: 2 in BRCA1 and 1 in BRCA2, which accounts for 2/24 (8%) of the total mutations detected in BRCA1 and 1/23 (4%) of the mutations in BRCA2 detected in this cohort. Notably, the family history of the individuals with these mutations is largely unremarkable suggesting that family history alone is a poor predictor of mutation status in Asian families. In conclusion, this study in a multi-ethnic (Malay, Chinese, Indian) cohort suggests that large genomic rearrangements are present at a low frequency but should nonetheless be included in the routine testing for BRCA1 and BRCA2.